Quality assurance in education: perception of undergraduate health professions students in a Malaysian university - Hui Meng Er; Vishna Devi Nadarajah; Sook Han Ng; Ann Nee Wong (Korean Journal of Medical Education, 2020)
Purpose Direct student involvement in quality processes in education has been suggested to encourage shared responsibilities among faculty and students. The objectives of this study were to explore undergraduate health professions students’ understanding of quality assurance (QA) in education, and identify the challenges and enablers for student involvement in an Asian context. Methods Twenty semi-structured interviews were conducted among medical, dentistry, and pharmacy students in a Malaysian University. The interviews were audio-recorded, transcribed verbatim, and thematically analyzed to understand the students’ perspectives of QA in education. Results The participants recognized the importance of QA towards ensuring the quality of their training, which will consequently impact their work readiness, employability, and quality of healthcare services. Academic governance, curriculum structure, content and delivery, faculty and student quality, teaching facilities, and learning resources were indicated as the QA areas. The challenges for students’ involvement included students’ attitude, maturity, and cultural barrier. To enhance their buy-in, clear objectives and impact, efficient QA mechanism, and recognition of students’ contribution had been suggested. Conclusion The findings of this study support student-faculty partnership in QA processes and decision making.